Optimal cultivation towards enhanced algae-biomass and lipid production using Dunaliella tertiolecta for biofuel application and potential CO2 bio-fixation: Effect of nitrogen deficient fertilizer, light intensity, salinity and carbon supply strategy. (1st April 2018) - Kumar, Anup; Guria, Chandan; Pathak, Akhilendra K.
Abstract: Fertilizer assisted optimum culture medium was formulated to enhance the productivity of Dunaliella tertiolecta productivity for biofuel feedstock by selecting the appropriate environmental and nutrient parameters involving 100% CO2 . The influences of NPK-fertilizer, NaCl and NaOH loading along with light intensity were investigated to maximize algae-biomass growth, lipid productivity and CO2 sequestration. Five-level and four-factor response surface method (RSM) was used for optimization. The optimum algal cultivation based on RSM technique was compared with simple genetic algorithm (SGA) technique and standard artificial seawater (ASW) based f/2 culture medium. Significant improvement in algae-biomass growth and lipid productivity was obtained along with the enhancement of CO2 sequestration using RSM- and SGA-oriented culture medium over standard ASW-based f/2 medium. Several multi-objective optimization problems involving conflicting objectives (algae-biomass growth, lipid productivity, CO2 sequestration and cultivation cost) were formulated and solved using the elitist non-dominated sorting genetic algorithm. The non-dominated Pareto-optimal solutions were obtained for all multi-objective optimization problem studied. The effects of fertilizer, NaCl and NaOH loading, light intensity and their interacting effects on algae-biomass growth, lipid productivity and CO2 sequestration were revealed successfully. Finally, volumetric mass transfer coefficient of CO2 was determined to link the operating variables with algae-biomass growth while cultivation. Highlights: Fertilizer and 100% CO2 assisted Dunaliella tertiolecta cultivation. CCD-RSM and genetic algorithm technique to formulate optimum culture medium. Multi-objective optimization to maximize algae-biomass for biofuel feed stock. Enhancement of biomass productivity, lipid-productivity and CO2 sequestration. Minimization of algal cultivation cost.